Aklimatisasi dan Evaluasi Produksi Mutan Rumput Gajah Kultivar Taiwan - Berlin Gea; Panca Karti; Iwan Prihantoro; A Husni (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2019)
Cultivation of the Elephant Grass cv Taiwan with tissue culture requires an acclimatization stage, therefore this study aims to find the best planting media and the effect of plant age and evaluation of production elephant grass cv taiwan mutant and nutrient content. Acclimatization was carried out in a greenhouse using sand, soil, and a combination of 50% sand with 50% soil, and the mutant type T2, T4 and K4. The acclimation process uses the Factorial RAL method with factor A type of mutant and factor B type of planting media and the parameters assessed are leaf length, number of leaves and plant mortality rate. Production evaluation uses the RAL method and the parameters observed to see elephant grass production are plant height, stem diameter, leaf width, number of tillers and amount of plant biomass production. Proximate analysis is used to show the nutritional value of plants that have been selected individually using scoring assessments. The results of the acclimatization study showed that the planting media that had the lowest mortality rate were sand and soil combination media (22%) followed by soil planting media (27%) and the planting media that had the highest mortality rate was sand media (30%). The results of the production evaluation stage showed that the highest average harvest weight was found in T4 mutants with an average weight of 1353 g clump-1harvest-1, followed by T2 mutants which had an average of 1198 g clump-1harvest-1 and the lowest harvest weight was found in K4 mutants with an average of 1002 g clump-1harvest-1. Based on the research results obtained the best planting media for the acclimation process of elephant grass cv Taiwan mutants is a combination of sand and soil media (1:1). The results of the evaluation stage of T4 mutant production are the best mutants based on morphological performance and production of plant biomass. Proximate analysis of selected plants shows that plants with mutant T2PT7 species have the best nutritional value, with nutritional content of PK 11.71% and SK 24.67%. Keywords : acclimatization, Elephant grass cv Taiwan, proximate analysis